MARKETING MARGINS ANALYSIS OF SEED COTTON IN DISTRICT KHANEWAL, PAKISTAN (Pakistan Journal of Science, 2022)
This paper attempts to estimate marketing margins of major intermediaries involved in the marketing of seed cotton in district Khanewal using primary source of data. Formal interviews were conducted from a representative sample of 80 cotton growers, 40 beoparies, 40 commission agents and 40 ginners selected using stratified random sampling technique. The findings of the study indicate that village beoparies (traders) earned gross marketing margin of Rs. 72 per maund (40 Kg), net margin of Rs. 26 per maund and 3.73% margin in marketing chain of seed cotton in district Khanewal. Commission agents earned Rs.35 per maund as gross marketing margin, Rs.23 per maund as net margin and 1.85% margin in marketing chain. The gross marketing margin of ginner was estimated as Rs.136 per maund, net margin as Rs. 45 per maund and 6.56% margin in marketing chain. The study suggests rationalising the role of middleman to economize and justified margins in the marketing chain of seed cotton in district Khanewal.
Keywords: Seed Cotton; Marketing Margin; Stratified Random Sampling